(untitled) (Islas, 2023)
Introduction: This article aims to present, from a feminist perspective, the community relations and cooperation within the framework of the implementation of the Peace Agreement in Colombia and its public policies for social inclusion, community integration, and autonomy. Methods: The dialogical method is used to compare integration policies, the community’s experience and position regarding the implementation, and the breaking of traditional epistemologies. Community relations are approached from a feminist perspective and community self-development. Results: This experience, supported and promoted through public policies, combined with community interest and engagement, results in proposals for community self-development in the following ways: i) active and differentiated participation in the implementation of public policy; ii) the decision to collectively inhabit and care for the community; and iii) the struggle for a life free from violence. Conclusions: It can be concluded that these alternative ways of inhabiting have promoted disruptive and emancipatory community processes and projects, breaking inherited patriarchal logics, reducing gender gaps, and building knowledge for the political transformation of reality.